A comparative study of the density of surface states in solid and hollow TiO2 microspheres. Issue 9 (3rd August 2018) - Gao, Chun; Peng, Yu-Qi; Hu, Lin-Hua; Mo, Li-E; Zhang, Xian-Xi; Hayat, Tasawar; Alsaedi, Ahmed; Dai, Song-Yuan
Abstract : The density of surface states and charge transport of TiO2 microspheres with different structures were investigated. Abstract : As a crucial photoelectric material, TiO2 microspheres have been widely applied as photoanodes in photovoltaic devices owing to their large surface area, suitable pore size and prominent scattering effect. However, surface states in the TiO2 films playing a significant role in the charge transport process are an important factor influencing the photovoltaic performance. Herein, solid and hollow TiO2 microspheres were compared to investigate the influence of the density and distribution of surface states. The density and distribution of surface states, charge recombination process and band edge shifts were investigated. The results showed that the density of surface states of the TiO2 microspheres decreased after recrystallization, leading to a suppressed charge recombination rate. Moreover, owing to the hollow architecture, recrystallized hollow microspheres (rHM) have higher photon utilization. As a result, a photoelectric conversion efficiency of dye-sensitized solar cells based on the rHM up to 10.57% was obtained.